PEMAKAIAN CADAR PADA MAHASISWI “MUSLIMAH MOTIVATIONS RIAU” DI PEKANBARU (SEBUAH ANALISIS DRAMATURGI TENTANG PEMAKAIAN CADAR) - Agustina "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The phenomenon of the veil in Indonesia has been around for a long time, even before Indonesia's independence. However, the discussion of veiled women is still very interesting to study. Their existence is often associated with radical Islam and acts of terrorism that often occur in Indonesia. So that the presence of veiled women raises pro and contra actions in society, therefore this study aims to determine the background and behavior of veiled female students as the reality of the back stage, and the obstacles or challenges that are passed in building the front stage. front). ) analysis of levels of dramaturgical female students. This study used a descriptive qualitative research method, the subjects in this study were 4 veiled female students as subjects and 4 biological parents of the subjects as research informants. In collecting data using observation techniques, in-depth interviews and documentation. The results in this study show that the background of veiled female students is not a graduate of Islamic boarding schools, they do not get support from their families to use the veil, while the motivation of female students in wearing the veil is because of social needs, there is an invitation from friends, because of the need for safety to feel comfortable when wearing the veil, the need for appreciation because they are embarrassed not to use the veil, then the last motivation for female students in using the veil is because of social needs there is an invitation from friends to use the veil which is caused by a broken heart and wanting a change in life leading to better things emigrated. In everyday life, the self-image displayed by veiled female students is inverted from the self-image shown on the front stage. which is the behavior of veil students when at home backstage female members of Mumo Riau do not use robes, syar'i headscarves, veils, and other attributes that describe pious women, because of challenges or obstacles experienced. the subject said that he did not receive support from his family to always use the veil, in public places he often received cynical glances from strangers, and it was difficult for others to recognize him because when he wore the veil only his eyes were visible. Keywords: Veil, Dramaturgy, Muslimah, Motivations, Veil Behavior